Burns a practical approach to immediate treatment and long term care - Sheridan, Robert Leo (Manson, 2012)
This book emphasizes the fundamental surgical, medical and related procedures involved in each stage of burn care, thus enabling the reader to focus on the essentials, and ensure the best outcome for patients. Chapters range from burn physiology, initial care and resuscitation, to wound evaluation and surgical management, respiratory and critical care, rehabilitation, reconstruction and aftercare. The book's concise visual approach will appeal to all professionals caring for burn patients in acute or recovery phases.